Tập luật lệ vè̂ tư-pháp : theo các văn bản đã công bó̂ đé̂n ngày 10-7-1957 (Vietnamese law coll. (Harvard Law School), 1957)
Abstracts of laws and regulations classified in 6 categories: judicial organization, democratic freedoms, criminal law, civil and commercial law, legislation, promulgation and application of law, procedural law.